Different Implications of Heart Failure, Ischemic Stroke, and Mortality Between Nonvalvular Atrial Fibrillation and Atrial Flutter—a View From a National Cohort Study - Yu‐Sheng Lin; Tien‐Hsing Chen; Ching‐Chi Chi; Ming‐Shyan Lin; Tao‐Hsin Tung; Chi‐Hung Liu; Yung‐Lung Chen; Mien‐Cheng Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundAtrial flutter (AFL) has been identified to be equivalent to atrial fibrillation (AF) in terms of preventing ischemic stroke, although differences exist in atrial rate, substrate, and electrophysiological mechanisms. This study aimed to investigate differences in clinical outcomes between nonvalvular AF and AFL. Methods and ResultsAF and AFL patients without any prescribed anticoagulation were enrolled from a 13‐year national cohort database. Under series exclusion criteria, ischemic stroke, heart failure hospitalization, and all‐cause mortality were compared between the groups in real‐world conditions and after propensity score matching. We identified 175 420 patients in the AF cohort and 6239 patients in the AFL cohort, and the prevalence of most comorbidities and frequency of medications were significantly higher in the AF group than the AFL group. In the real‐world setting the AF patients had higher incidence rates of ischemic stroke, heart failure hospitalization, and all‐cause mortality than the AFL patients (all P<0.001). After propensity score matching, the incidence rate of ischemic stroke in the AF cohort was 1.63‐fold higher than in the AFL cohort (P<0.001), the incidence rate of heart failure hospitalization in the AF cohort was 1.70‐fold higher than in the AFL cohort (P<0.001), and the incidence rate of all‐cause mortality in the AF cohort was 1.08‐fold higher than in the AFL cohort (P=0.002). ConclusionsThere were differences between AF and AFL in comorbidities and prognosis with regard to ischemic stroke, heart failure hospitalization, and all‐cause mortality.